3D imaging and manipulation of subsurface selenium vacancies in PdSe 2 - Nguyen, Giang D. (2018)
Two-dimensional materials such as layered transition-metal dichalcogenides (TMDs) are ideal platforms for studying defect behaviors, an essential step towards defect engineering for novel material functions. Here, we image the 3D lattice locations of selenium-vacancy VSe defects and manipulate them using a scanning tunneling microscope (STM) near the surface of PdSe2, a recently discovered pentagonal layered TMD. The VSe show a characterisitc charging ring in a spatially resolved conductance map, based on which we can determine its subsurface lattice location precisely. Using the STM tip, not only can we reversibly switch the defect states between charge neutral and charge negative, but also trigger migrations of VSe defects. This allows a demonstration of direct “writing” and “erasing” of atomic defects and tracing the diffusion pathways. First-principles calculations reveal a small diffusion barrier of VSe in PdSe2, which is much lower than S vacancy in MoS2 or an O vacancy in TiO2. This finding opens an opportunity of defect engineering in PdSe2 for such as controlled phase transformations and resistive-switching memory device application.